Attitudes of nurses toward telenursing and influencing factors in resource-limited settings: Northwest Ethiopia 2022 - Butta, Fikadu Wake; Tilahun, Biniyam Chaklu; Endehabtu, Berhanu Fikadie; Shibabaw, Adamu Ambachew; Chereka, Alex Ayenew; Gebeyew, Ayenew Sisay; Reda, Mekides Molla; Kitil, Gemeda Wakgari; Nimani, Teshome Demis (Frontiers in Digital Health, 2025)
BackgroundThe worldwide scarcity of nurses is a pressing concern, with the World Health Organization predicting a deficit of 5.9 million nurses globally by 2025. Notably, 89% of this shortage is expected to impact low- and middle-income countries. To address the growing demand for nursing professionals, the concept of telenursing care is being considered. However, there is limited evidence regarding nurses' attitudes towards telenursing care in Ethiopia. This study aims to understand how nurses feel about telenursing care and the factors related to it at a specialized teaching referral hospital in northwest Ethiopia.MethodWe conducted a cross-sectional study at a specialized teaching referral hospital, employing a simple random sampling technique to gather information from 423 nurses. The study took place from July 28 to December 19, 2022/23. Descriptive statistics, including tables and bar graphs, were utilized. Additionally, a binary logistic regression analysis was conducted with 95% confidence intervals and a significance level of P < 0.05 to identify factors influencing nurses' attitudes toward telenursing.ResultOut of the total 416 nurses who responded, representing a response rate of 98.35%, 39.7% exhibited favorable attitudes towards telenursing care. Factors associated with nurses' attitudes included awareness, source of information, social media use, knowledge, computer access, digital training, internet access, and computer training.ConclusionsThe findings indicate a low level of positive attitudes towards telenursing care among nurses. To enhance future acceptance, use, and implementation, policymakers, higher education institutions, and other stakeholders should collaborate to improve nurses' attitudes toward telenursing care, taking into consideration various factors and user preferences.